Isolated talus dislocation: a case report - Farias Molina, Wellington; Bottino Martins, Guilherme; Martins Pimenta, Luiz Sergio; Galizia Heitzmann, Lourenço; Souza Campana, Mayra; Saori Gushiken, Erika (Journal of the Foot & Ankle, 2022)
Peritalar dislocation is a rare injury, usually associated with fractures. It mainly affects males in high-energy traumas such as falls from height, car accidents, or even torsional traumas during the practice of sports activities. This study illustrates a case attended by the authors to discuss peritalar dislocation and its diagnosis, classification, treatment, and prognosis. Such injury may evolve with complications if not properly managed, including ankle movement pain, joint stiffness, deformities, post-traumatic arthrosis, and even osteonecrosis. Level of Evidence V; Therapeutic Studies; Expert Opinion.